Graph algorithms - Even, Shimon (Cambridge ; New York : Cambridge University Press, 2012)
"Shimon Even's Graph Algorithms, published in 1979, was a seminal introductory book on algorithms read by everyone engaged in the field. This thoroughly revised second edition, with a foreword by Richard M. Karp and notes by Andrew V. Goldberg, continues the exceptional presentation from the first edition and explains algorithms in a formal but simple language with a direct and intuitive presentation. The book begins by covering basic material, including graphs and shortest paths, trees, depth-first-search, and breadth-first search. The main part of the book is devoted to network flows and applications of network flows, and it ends with chapters on planar graphs and testing graph planarity"--Provided by publisher.
"Shimon Even's Graph Algorithms, published in 1979, was a seminal introductory book on algorithms read by everyone engaged in the field. This thoroughly revised second edition, with a foreword by Richard M. Karp and notes by Andrew V. Goldberg, continues the exceptional presentation from the first edition and explains algorithms in a formal but simple language with a direct and intuitive presentation. The book begins by covering basic material, including graphs and shortest paths, trees, depth-first-search, and breadth-first search. The main part of the book is devoted to network flows and applications of network flows, and it ends with chapters on planar graphs and testing graph planarity"--Provided by publisher.
Machine generated contents note: 1. Paths in graphs; 2. Trees; 3. Depth-first search; 4. Ordered trees; 5. Flow in networks; 6. Applications of network flow techniques; 7. Planar graphs; 8. Testing graph planarity.
Includes bibliographical references and index.
Keywords: Graph algorithms